Abundance and Equality - Kop, Mauritz (Frontiers in Research Metrics and Analytics, 2022)
1. The technology driven post-scarcity society is upon us. Ubiquitous technologies are eradicating scarcity in many industries. These macroscopic system trends are causing our economy to transition from relative scarcity to relative abundance. For many people in the world however, in both developed, developing, and underdeveloped countries, the notion of an Age of Abundance will sound utterly bizarre. There is a tension between abundance and equality. 2. Good governance considers in what manner the state conducts public policy, manages public resources and promotes overall prosperity. This chapter connects good governance to the end of scarcity and integrates equality into abundance. 3. The chapter critically examines the normative justifications of our scarcity based legal institutions, such as property and intellectual property (IP) systems, in light of 10 exponential, Fourth Industrial Revolution (4IR) technologies, and the post scarcity economy. 4. Starting point is that absolute and relative abundance are not utopian. Technology will erase scarcity in more and more economic areas in the foreseeable future, but not everywhere or for everybody. The chapter views relative scarcity and relative abundance as temporal socio-economic categories at two opposite sides of a continuum. 5. The chapter unifies good governance with equality and abundance, by introducing a post-Rawlsian Equal Relative Abundance (ERA) principle of distributive justice. This includes defining a set of material and immaterial primary goods, warranting adequate, sufficient levels of relative abundance (which depend on technological evolution), and equitable results per region or group. Crucially, ERA integrates desert-based principles to the degree that some may deserve a higher level of material goods because of inequality in contributions, i.e. their hard work, talent, luck or entrepreneurial spirit, only to the extent that their unequal rewards do also function to improve the position of the least advantaged. 6. A society governed by the ERA principle should in theory be able to solve the poverty trap on a global level. As lifting people from poverty in Europe is a different thing than achieving ERA in the US, applying equal relative abundance techniques in Asia and Africa each have their own specific challenges and dimensions.